The Pragmatic Theory of Meaning - Piotr Szałek (Studia Semiotyczne, 2025)
The paper addresses the proto-pragmatic theory of meaning formulated by Kazimierz Ajdukiewicz (1890-1963), one of the most prominent inter-war Polish analytic philosophers from a philosophical school called the Lvov-Warsaw School. The paper finds a point of intersection between analytic philosophy and pragmatism on the basis of this particular case study and places Ajdukiewicz’s theory in close proximity to the so-called semantic pragmatism of Robert B. Brandom (1950-). The paper argues that there are three particular spheres where we can detect a striking similarity between the two standpoints, which could both be described as exemplifications of analytic pragmatism. The first sphere of similarity is their description of the dominance of pragmatics over semantics. The second sphere of similarity concerns the so-called pragmatic mediation of semantic relations (using a phrase coined by Brandom). And the third similarity regards the concept of the rules of assertions.